Multifaceted Contributions by Different Regions of the Orbitofrontal and Medial Prefrontal Cortex to Probabilistic Reversal Learning - Dalton, Gemma L. (J Neurosci, 2016)
Different subregions of the prefrontal cortex (PFC) contribute to the ability to respond flexibly to changes in reward contingencies, with the medial versus orbitofrontal cortex (OFC) subregions contributing differentially to processes such as set-shifting and reversal learning. To date, the manner in which these regions may facilitate reversal learning in situations involving reward uncertainty remains relatively unexplored. We investigated the involvement of five distinct regions of the rat OFC (lateral and medial) and medial PFC (prelimbic, infralimbic, and anterior cingulate) on probabilistic reversal learning wherein “correct” versus “incorrect” responses were rewarded on 80% and 20% of trials, respectively. Contingencies were reversed repeatedly within a session. In well trained rats, inactivation of the medial or lateral OFC induced dissociable impairments in performance (indexed by fewer reversals completed) when outcomes were probabilistic, but not when they were assured. Medial OFC inactivation impaired probabilistic learning during the first discrimination, increased perseverative responding and reduced sensitivity to positive and negative feedback, suggestive of a deficit in incorporating information about previous action outcomes to guide subsequent behavior. Lateral OFC inactivation preferentially impaired performance during reversal phases. In contrast, prelimbic inactivation caused an apparent improvement in performance by increasing the number of reversals completed. This was associated with enhanced sensitivity to recently rewarded actions and reduced sensitivity to negative feedback. Infralimbic inactivation had no effect, whereas the anterior cingulate appeared to play a permissive role in this form of reversal learning. These results clarify the dissociable contributions of different regions of the frontal lobes to probabilistic learning. SIGNIFICANCE STATEMENT The ability to adjust behavior in response to changes involving uncertain or probabilistic reward contingencies is an essential survival skill that is impaired in a variety of psychiatric disorders. It is well established that different forms of cognitive flexibility are mediated by anatomically distinct regions of the frontal lobes when reinforcement contingencies are assured, however, less is known about the contribution of these regions to probabilistic reinforcement learning. Here we show that different regions of the orbitofrontal and medial prefrontal cortex make distinct contributions to probabilistic reversal learning. These findings provide novel information about the complex interplay between frontal lobe regions in mediating these processes and accordingly provide insight into possible pathophysiology that underlies impairments in cognitive flexibility observed in mental illnesses.